2017
DOI: 10.1016/j.cbpc.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the antioxidant responses and lipid peroxidation of two species of tadpoles (Rhinella schneideri and Physalaemus nattereri) exposed to the herbicide sulfentrazone (Boral 500SC®)

Abstract: Amphibians can experience large temperature fluctuations in their habitats, especially during the larval stage, when tadpoles are restricted to small and ephemeral ponds. Changes in water temperature can alter development, metabolism and behaviour of cold-blooded animals but also the toxicokinetics of chemicals in the environment. In Brazil, pesticides application is intensified during the rainy season, which is the period of reproduction for many amphibian species. We evaluated here the influence of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Studies report possible herbicide concentrations that may be available in aquatic habitats after leaching (Thorngren et al 2017). Freitas et al (2017) used Boral® 500 SC-sulfentrazone concentrations of 10, 50, and 100 μg/L in exposure experiments using Rhinella schneideri and Physalaemus nattereri tadpoles.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies report possible herbicide concentrations that may be available in aquatic habitats after leaching (Thorngren et al 2017). Freitas et al (2017) used Boral® 500 SC-sulfentrazone concentrations of 10, 50, and 100 μg/L in exposure experiments using Rhinella schneideri and Physalaemus nattereri tadpoles.…”
Section: Experimental Designmentioning
confidence: 99%
“…The authors demonstrated that energetic reserves (glycogen, lipids, triglycerides, and proteins) of gills, liver, and muscles were completely depleted. Freitas et al (2017), performed one of the few studies about the effects of Boral® 500SC (active ingredient-sulfentrazone) on amphibians. The authors evaluated the influence of different temperatures (28, 32, and 36 °C) and concentrations of sulfentrazone (10, 50, and 100 μg/L) in Physalaemus nattereri and Rhinella schneider tadpoles in oxidative stress biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a phase II detoxification enzyme, GST protects cells and tissues against oxidative stress by catalyzing the conjugation of the reduced form of glutathione to various xenobiotic substrates ( Hayes and Strange, 1995 ). The above-mentioned antioxidant enzyme activities alteration has been widely used as biochemical biomarkers for oxidative stress caused by environmental stressors ( Matozzo et al, 2013 ; Nogueira et al, 2015 ; Freitas et al, 2017 ). Based on this study, antioxidant enzymes (CAT, SOD, and GST) were generally stimulated in the digestive glands of both oysters and scallops, indicating that the antioxidant system was activated in response to the induction of oxidative stress caused by STX exposure.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the effects of sulfentrazone in nontarget aquatic species other than those conducted by the US Environmental Protection Agency (USEPA) for sulfentrazone, and these studies indicate that nontarget aquatic vascular plants are the most susceptible to sulfentrazone, followed by phytoplankton, aquatic invertebrates, and fish (Thorngren et al 2017). Sulfentrazone can have negative effects on amphibians, as evidenced by Freitas et al (2017) where the herbicide caused the disruption of the oxidative balance of two species of amphibians native to Brazil (Rhinella schneideri and Physalaemus nattereri). Wilkens et al ( 2019) also observed changes in the energy reserves, plasma corticosterone, and oxidative balance of bullfrog tadpoles (Rana catesbeiana) exposed to Boral® 500SC.…”
Section: Introductionmentioning
confidence: 99%